Chile Financial Sector Assessment Program : Detailed Assessment Report of the Responsibilities of the Authorities - World Bank Group (World Bank, Washington, DC, 2016)
The Central Bank of Chile (Banco Central de Chile, BCCh) and Chile’s Ministry of Finance, requested the World Bank to undertake a stand-alone Review of Standards and Codes (ROSC) module of the Principles for Financial Market Infrastructures (PFMI) of the Committee on Payments and Market Infrastructures (CPMI) and the International Organization of Securities Commission (IOSCO). total of five financial market infrastructures (FMIs) were assessed as part of this ROSC, although one of these operates both as a central counterparty (CCP) and as a securities settlement system (SSS) for different segments of the exchange-traded securities market, and as a result a total of six FMI assessments were produced by the team. In addition, the Responsibilities of Authorities for FMIs were assessed. On this basis, the World Bank Group (WBG) team and the local team conducted detailed interviews with senior and mid-level managers of all the respective institutions, and prepared the assessment reports. In addition to the self-assessments, other sources of information included the applicable laws and regulations, as well as each FMI’s main policies and internal documents (e.g. detailed policies, and processes and procedures for certain key areas) which were shared by the FMIs with the assessors, and other information available at each FMI’s website (e.g. statistics). The WBG and local teams also met with a number of users of these FMIs, including two large commercial banks and two brokers-dealers that are not part of local bank-lead conglomerates. The assessment report covers the Responsibilities of central banks, market regulators, and other relevant authorities for the above-mentioned financial market infrastructures